The The Correlation between students’ reading interest and Their reading comprehension at the ninth grade of MTs N 1 Lampung Utara academic year 2021/2022: Hubungan Antara minat baca siswa dan pemahaman membaca siswa pada kelas sembilan dari MTs N 1 Lampung Utara tahun akademik 2021/2022 - Pratama, Yuda (Griya Cendikia, 2022)
This study intends to investigate the phenomenon of students’ reading interest that can be related to their reading comprehension. The purpose of this study is to find out whether there is significant correlation between students’ reading interest and their reading comprehension at the ninth grade of MTs N 1 Lampung Utara academic year 2021/2022. The kind of this research is quantitative research and used correlational research design. The population consisted of 192 students. The sample was taken 15% of the population from each class, so the total sample was 29 students from each class. The instrument used in this research were questionaire and test with multiple choice form. Then, to fullfil the hypothesis of the research, the researcher analyzed data by using the formula of pearson product moment correlation and resulted Robserved = 0.442 then, resulted the value of Tobserved>Ttable was 2,561>2,045. Based on the result data analysis, it is concluded that Ho was rejected and Ha was accepted, It means that there is a significant correlation between the Students’ Reading Interest and Their Reading Comprehension. Keywords : Reading Interest, Reading Comprehension, Students.